From French Education to National Contributions, Nguyen Van Huyen’s Advocacy for Vietnamese Language Teaching and Educational Method Innovations for Developing the New Education System in Vietnam Post-1945 - Khuong, Nguyen Duc; Ngo, Nguyen Van; Nguyen, Le Chi; Hung, Mai Van (Journal of Ecohumanism, 2024)
In Vietnam at the beginning of the 20th century, influenced by both domestic and international historical changes and transformations in Franco-Vietnamese education, many patriotic youths pursued academic studies and scientific research to contribute towards raising the national intellect, strengthening national spirit, and improving public welfare. Whether educated domestically or abroad, these young intellectuals, overcoming significant difficulties, were thoroughly trained by advanced educational systems and thus emerged as a generation of distinguished scholars—the "golden intellectuals" of modern Vietnam. This group significantly influenced modern Vietnamese education, among whom Nguyen Van Huyen notably contributed to establishing the foundations of the country’s new educational system after 1945. His efforts amidst severe challenges, such as prolonged wars and national division, provided a solid foundation for the gradual development and strengthening of Vietnam’s basic education system.